A Farewell to Alms: A Brief Economic History of the World - Heller, Henry (Labour / Le Travail, 2009)
The article reviews the book, "A Farewell to Alms: A Brief Economic History of the World," by Gregory Clark.
Keywords: BOOKS -- Reviews; CLARK, Gregory, 1957-; Economic history; FAREWELL to Alms: A Brief Economic History of the World, A (Book); Nonfiction